ATTRIBUTIONS FOR SUCCESS AND FAILURE IN SPANISH TEAM SPORT PLAYERS - R. González-Boto; O. Molinero; R. Martínez; S. Márquez (Asociación Española de Ciencias del Deporte, 2010)
ABSTRACT This study examined the role of ability, effort, luck and difficulty of the task in attributions for successful and unsuccessful performances made by Spanish team sport players, and determined if differences exist between athletes at different competition levels. Participants were 143 young men (soccer: N = 64; indoor soccer: N = 37; basketball: N = 42), ages 17 to 25 years (M = 20, SD = 5). Winners perceived ability and effort as the reasons behind their success while losers made attributions mainly to luck and the difficulty of the task. Ability and effort were in the three sports the reasons given for successful outcomes at various competition levels. Difficulty of the task was the factor rated higher by those who lost competing at a national level, while luck and effort were rated higher for those who lost competing at a regional and local level. KEY WORDS: attribution, team sports. competition levels   RESUMEN En este estudio se analizaron el papel de la habilidad, el esfuerzo, la suerte y la dificultad de la tarea en las atribuciones de éxito y fracaso realizadas por practicantes españoles de deportes colectivos y se determinó si existían diferencias entre jugadores con distintos niveles de competición. Participaron 143 chicos (fútbol: N = 64; fútbol sala: N = 37; baloncesto: N = 42), con edades comprendidas entre 17 y 25 años (M = 20, SD = 5). Los ganadores consideraban la habilidad y el esfuerzo como las razones responsables de su éxito, mientras que los perdedores realizaban sus atribuciones principalmente a la suerte y a la dificultad de la tarea. En los tres deportes estudiados, la habilidad y el esfuerzo se consideraban como las principales razones del éxito en los diferentes niveles competitivos. La dificultad de la tarea era la causa más puntuada por los perdedores que competían a nivel nacional, mientras que a nivel regional y local se otorgaba mayor importancia a la suerte y al esfuerzo. Palabras clave: atribución, deportes colectivos, niveles de competición.